Can COVID 19 present like appendicitis? - Ahmed Abdalhadi (14152962) (2020)
Coronavirus disease -19 is a novel pandemic contagious respiratory infection that frequently presents with fever and dry cough. However, it can present with other rare symptoms. As this disease is a new disease, the full picture of the disease presentation is not yet clear, and it might present with symptoms and signs of other common diseases. Here, we report a 40 year old female who presented with acute onset nausea, vomiting, loss of appetite and vague abdominal pain as a clinical picture of appendicitis, but her CT abdomen image showed normal appendix, bilateral patchy peripheral lung basal consolidation, and ground-glass attenuation, so she was tested for coronavirus disease-19, which was positive. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00860